2014
DOI: 10.1155/2014/368640
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Appendectomy in Morbidly Obese Patient

Abstract: Introduction. Laparoscopic appendectomy has significant benefits in obese patients. However, morbid obesity can be accepted as an exclusion criterion for natural orifice transluminal endoscopic surgery (NOTES). Here, we present a transvaginal appendectomy in a 66-year-old morbidly obese (BMI 36 kg/m2, ASA III) patient. Case and Technique. Acute appendicitis was suspected based on history, physical examination, laboratory tests, and ultrasound findings. During laparoscopic surgery, a 5 mm trocar was inserted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In effect, this discourages scissor-configuration of working instruments, an oft-reported difficulty of traditional transvaginal NOTES (Figure 2). 13,16,33 These tactical adaptations offer an enormous ergonomic advantage, while manipulating two vaginal working ports, to dissect the appendix and prevent unwarranted pelvic bowel injuries, not infrequently reported in the literature. 33 Though the entry points for the vaginal trocars remain at the same level, one of them occupies a deeper position than the other to create an intentional intra-corporal length mismatch.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In effect, this discourages scissor-configuration of working instruments, an oft-reported difficulty of traditional transvaginal NOTES (Figure 2). 13,16,33 These tactical adaptations offer an enormous ergonomic advantage, while manipulating two vaginal working ports, to dissect the appendix and prevent unwarranted pelvic bowel injuries, not infrequently reported in the literature. 33 Though the entry points for the vaginal trocars remain at the same level, one of them occupies a deeper position than the other to create an intentional intra-corporal length mismatch.…”
Section: Discussionmentioning
confidence: 99%
“…Natural orifice transluminal endoscopic surgery (NOTES) has been predicted to replace conventional laparoscopy in the near future. [1][2][3][4][5][6][7][8][9][10] In addition, the transvaginal route, having typical physical and physiological benefits, [1][2][3][4][5][6][11][12][13][14][15][16] makes it the safest, as well as an immensely popular method. [1][2][3]6,[11][12][13][14][15][17][18][19][20][21][22][23][24][25][26] However, even a decade after its inception, it continues to be fraught with diverse technical hurdles such as spatial constraints, inadvertent vaginal gas-leak, compelling requirements for complex instrumentation, scarce availability and affordability, and a steep learning curve, to name a few.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women were excluded if they had retrocecal appendix, were pregnant, had past abdominal or gynecological surgery, had complicated appendicitis like appendicular abscess, were virgins, had gynecological infections, aged <18 or >65, had pelvic adhesions, had prior malignancy, chemotherapy, or BMI >35 kg/m 2 [ 13 , 16 - 20 , 22 ]. Despite the BMI limitations, two publications performed surgery on women with a BMI over 35 kg/m 2 to test whether it is a true contraindication [ 23 , 25 ]. Another two publications only performed TVA in patients undergoing laparoscopic vaginal hysterectomy as they were already performing a vaginal surgery [ 19 , 21 ].…”
Section: Reviewmentioning
confidence: 99%
“…German registry showed that more than 6% [182 cases] of human NOTES procedure was appendicectomy done by Tg and Tv routes. Not only slim patients but also morbidly obese patients benefited from NOTES appendicectomy [124]. A 5-mm trocar was inserted through the umbilicus and a 5-mm telescope was placed.…”
Section: Appendicectomymentioning
confidence: 99%